Lanthanoid Complexation by a Tris-Tetrazole-Functionalised Calix[4]arene - D'Alessio, D.; Skelton, B.; Sobolev, A.; Krause-Heuer, A.; Fraser, B.; Massi, Massimiliano; Ogden, Mark (Wiley - V C H Verlag GmbH, 2016)
The synthesis and characterization of 5,11,17,23-tetra-tert-butyl-25-hydroxy-26,27,28-tris(tetrazol-5-ylmethoxy)calix[4]arene is reported. Purification of the macrocycle required the use of preparative HPLC techniques. The macrocycle was found to be a poorer ligand for complexation of lanthanoid cations than the bis(tetrazole) analogue, but somewhat more effective than the tetrakis(tetrazole)-substituted derivative. Two metal complexes of the tris(tetrazole)-calixarene were structurally characterised. A polymeric sodium salt of the tris(tetrazole)-calixarene was isolated from a solution containing yttrium and a sodium acetate buffer. A praseodymium complex was isolated in the presence of an ammonium acetate buffer, where the calixarene acts as a unidentate ligand, bound to the metal atom through one tetrazole N-atom. Increasing the amount of buffer resulted in the crystallisation of a metal-free ammonium salt of the calixarene.